Near Field and Far Field Calculation from Metallic Elliptical Cylinder Coated with Left-Handed Metamaterial - Ho, Manh Linh; Ta, Son Xuat; Kiem, Nguyen Khac; Dao, Ngoc Chien (Old Journal, 2018)
Recently, there is an increasing demand for metamaterial research both in theory and practical designs. Metamaterial cloaks and partially filled waveguide have been considered for their potential radiation enhancement and electromagnetic field confinement of sources. For some particular cases, the analysis can be carried out by separation of variables with the use of special functions. This paper present a two-dimensional problem of electromagnetic scattering from line source located outside of a metallic elliptical cylinder coved by isorefractive (right-handed material) and anti-isorefractive dielectric (left-handed material) . Analytical solutions of electric and magnetic fields as functions of line source position and layer thickness are discussed in frequency domain.